Platelet receptors as therapeutic targets: Past, present and future - Jamasbi, Janina; Ayabe, Keng; Goto, Shinya; Nieswandt, Bernhard; Peter, Karlheinz; Siess, Wolfgang (Thrombosis and Haemostasis, 2017)
Anti-platelet drugs reduce arterial thrombosis after plaque rupture and erosion, prevent stent thrombosis and are used to prevent and treat myocardial infarction and ischaemic stroke. Some of them may also be helpful in treating less frequent diseases such as thrombotic thrombocytopenic purpura. The present concise review aims to cover current and future developments of anti-platelet drugs interfering with the interaction of von Willebrand factor (VWF) with glycoprotein (GP) Ibα, and directed against GPVI, GPIIb/IIIa (integrin αIIbβ3), the thrombin receptor PAR-1, and the ADP receptor P2Y12. The high expectations of having novel antiplatelet drugs which selectively inhibit arterial thrombosis without interfering with normal haemostasis could possibly be met in the near future.
Keywords: Antiplatelet agents; GP Ibα; GP VI; GP IIb/IIIa; PAR-1